Calculation of Stopping Power and Range of Nitrogen Ions with the Skin Tissue in the Energies of (1-1000) MeV - Yaqoob, Saad Nafea; Saied, Bashair Mohammed (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2018)
The use of heavy ions in the treatment of cancer tumors allows for accurate radiation of the tumor with minimal collateral damage that may affect the healthy tissue surrounding the infected tissue. For this purpose, the stopping power and the range to which these particles achieved of  Nitrogen (N) in the skin tissue  were calculated by programs SRIM (The Stopping and Range of Ions in Matter),(SRIM Dictionary) [1],(CaSP)(Convolution  approximation for Swift Particles )[2]which are famous programs to calculate stopping power of material and Bethe formula , in the energy range (1 - 1000) MeV .Then  the semi - empirical formulas to calculate the stopping power and range of Nitrogen ions in the skin tissue were founded from fitting for average the values which calculated by using these programs using (MATLAB2016) program,the maximum value of energy for Nitrogen ions can lose along its path in skin tissue is founded and the  range correspond to this value, the maximum range for Nitrogen ions can be reached in the skin tissue is founded too .The importance of the research is to know the data of thes particles and their use in treatment without causing a bad effect on the patient.